Mechanochemical preparation of metal/sulphide nanocomposite particles. (24th March 2005) - Balaz, Peter; Godocikova, Erika; Takacs, Laszlo; Gock, Eberhard
The mechanochemical reduction of stibnite (Sb2 S3 ), copper sulphide (Cu2 S), galena (PbS) and auripigment (As2 S3 ) with elemental Fe has been studied. Metallic Sb, Cu and Pb are obtained due to the reducing power of iron. The metal/sulphide nanocomposite particles have been characterised by XRD, SEM and TEM methods. The reduction processes are very straightforward and fast and can be carried out at ambient temperature.